MINERAL AND FLUID INCLUSIONS IN ZIRCON OF UHP METAMORPHIC ROCKS FROM THE CCSD-MAIN DRILL HOLE: A RECORD OF METAMORPHISM AND FLUID ACTIVITY - Zhang Z.; Shen K.; Xiao Y.; Hoefs J.; Liou J.G. (My University, 2006)
The Chinese Continental Scientific Drilling (CCSD) main drill hole (0-3000 m) in Donghai, southern Sulu orogen, consists of eclogite, paragneiss, orthogneiss, schist and garnet peridotite. Detailed investigations of Raman, cathodoluminescence, and microprobe analyses show that zircons from most eclogites, gneisses and schists have oscillatory zoned magmatic cores with low-pressure mineral inclusions of Qtz, Pl, Kf and Ap, and a metamorphic rim with relatively uniform luminescence and eclogite-facies mineral inclusions of Grt, Omp, Phn, Coe and Rt. The chemical compositions of the UHP metamorphic mineral inclusions in zircon are similar to those from the matrix of the host rocks. Similar UHP metamorphic P-T conditions of about 770 °C and 32 kbar were estimated from coexisting minerals in zircon and in the matrix. These observations suggest that all investigated lithologies experienced a joint in situ UHP metamorphism during continental deep subduction. In rare cases, magmatic cores of zircon contain coesite and omphacite inclusions and show patchy and irregular luminescence, implying that the cores have been largely altered possibly by fluid-mineral interaction during UHP metamorphism. Abundant H2O-CO2, H2O- or CO2-dominated fluid inclusions with low to medium salinities occur isolated or clustered in the magmatic cores of some zircons, coexisting with low-P mineral inclusions. These fluid inclusions should have been trapped during magmatic crystallization and thus as primary. Only few H2O- and/or CO2-dominated fluid inclusions were found to occur together with UHP mineral inclusions in zircons of metamorphic origin, indicating that UHP metamorphism occurred under relatively dry conditions. The diversity in fluid inclusion populations in UHP rocks from different depths suggests a closed fluid system, without large-scale fluid migration during subduction and exhumation. © 2006 Elsevier B.V. All rights reserved.
Keywords: CHINESE CONTINENTAL SCIENTIFIC DRILLING; DRILL CORE; FLUID EVOLUTION; MINERAL AND FLUID INCLUSIONS; UHP METAMORPHISM; ZIRCON